COMPETITIVIDAD PARA LAS MICRO, PEQUEÑAS Y MEDIANAS EMPRESAS EN MÉXICO, MEDIANTE LAS INCUBADORAS DE NEGOCIOS - Salas, Jorge Francisco; Valles, Elvia Karina; Galván, Ana Karina; Cuevas, Tomas (European Scientific Journal, ESJ, 2012)
The Micro, Small and Medium Enterprises (MSMEs) play an important role in the economy of Mexico, reaching regarded as the backbone of the national economy and employment. However, despite its importance, the average lifespan of MSMEs is only two years due to internal factors related to the manager or owner of the company and competitiveness. It is at this point that business incubators can be the conduits for carrying MSMEs towards market competitiveness and success. The present essay aims to encourage entrepreneurs to know how business incubators help develop positively major internal factors that MSMEs need to survive their early years, so have the opportunity to create and develop companies and positioned on a solid competitive market. This analysis was performed on data and results provided by related studies.